Comparison of Supercritical Fluid Extraction and Ultrasound-Assisted Extraction of Corchorus Olitorius L. and Evaluation of Their Antioxidant Properties and Identification of Compounds Using LC-ESI-MS - Hanieh Nasrollahi; Mehrnaz Karimi; Farhad Raofie (Tehran University of Medical Sciences, 2022)
Corchorus olitorius L. is a medicinal herb with anti-inflammatory, laxative, and tonic properties, which is effective on the treatment of cancer and tumors. In this study, the extraction efficiency of supercritical fluid extraction (SFE) and ultrasound-assisted extraction (UAE) of C. olitorius as well as their antioxidant activities were investigated by 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical. For this purpose, central composite block cube star and central composite design were employed to determine the optimal conditions. Thereafter, the qualification analysis of the effective ingredients of C. olitorius was done by LC-ESI-MS in negative mode. The results of LC-MS showed that C. olitorius includes phenolic and flavonoid compounds such as caffeic acid, p-coumaric acid, trans-ferulic acid, quercetin, naringenin, cirsiliol, cirsilineol, quercetrin, and naringin. Moreover, the SFE efficiency of extraction and IC50 value was obtained 4.25% and 1208.99 µg/mL, respectively. Also, the UAE efficiency of extraction and IC50 of antioxidant activity was obtained as 15.29% and 994.284 µg/mL, respectively. These results confirmed that the efficiencies of extraction and antioxidant activity of UAE were higher than that of SFE; however, the SFE is an environmentally friendly method and consumed less organic solvent.